Substance over style: is there something wrong with abandoning the white coat? - Palacios-González, César (J Med Ethics, 2015)
In this paper, we address points raised by Stephanie Dancer's article in The BMJ in which she claimed that by ‘dressing down’, physicians fail to adhere to the dignitas of the medical profession, and damage its reputation. At the beginning of this paper, we distinguish between two different senses in which a person can be, as she terms it, ‘scruffy’; and then we address Dancer's three main claims. First, we argue that in regard to the medical profession it is fallacious to assume, as she appears to do, that someone is incompetent or irresponsible when such a judgement is grounded in the fact that a physician is not dressed in a formal way. Second, we argue, contrary to her claim, that the dignified nature of the medical profession is in no coherent way linked to sartorial elegance or lack thereof, but rather, that such dignity is bound to the value of the medical practice in itself, to patients, and to society at large. Third, we examine two ways in which doctors can ‘dress down’ and show that ‘scruffiness’ does not necessarily intimates a lack of personal hygiene. Finally, we show that pointing to mere statistical correlation without causation, cannot be used as an argument against scruffiness. We conclude by suggesting that in the medical context, it is more appropriate to educate patients than to chastise practitioners for not following arbitrary cultural mores.